Penerapan Pewarnaan Graf pada Penjadwalan Mengajar Dosen Pendidikan Matematika Universitas Nurul Jadid - Farisi, Olief Ilmandira Ratu; Maysyaroh, Siti; Dewi, Eka Fitriana (Jurnal Matematika; Vol 11 No 1 (2021), 2021)
Learning schedules arrangement of lecturers in Mathematics Education Nurul Jadid University is still done manually by inserting lecturers' schedules one by one. Consequently, there are overlapping schedules that led to ineffective lecture preparation and cause confusion among lecturers and students. Besides, our Study Program only has two rooms which cause limited scheduling. One of the schedule arrangement techniques is graph coloring. In this technique, each vertex represents the course while the edge represents the course taught by the same lecturers or chosen by the same classes. By graph coloring, there will be an optimal schedule arrangement. In addition, the schedule is easily changed and reassembled in accordance with the group of colors.